Kinetics of commonly used blocking approaches in the game of volleyball - Cabarkapa, D.; Fry, A.; Cabarkapa, D.; Rogers, A.; Mosier, A. (The Journal of Strength and Conditioning Research, 2021)
Volleyball is a highly popular international sport where each player is required to know how to pass, set and serve the ball, and a majority of players need to be proficient with performing fundamental blocking and attacking approaches. Previous research found that the team that accumulates more blocks and points resulting from blocking formations is more likely to win a game. Purpose: The purpose of this study was to quantify and compare ground reaction forces (GRF) for the most commonly used volleyball blocking approaches. Methods: Eighteen healthy recreationally active women (hgt = 167.7 677.9 cm, wgt = 63.3 3.6.3 kg, age = 20.3 0.0.9 years) with previous competitive playing experience volunteered to participate in this research study. After a standardized warm-up, subjects performed 5 blocking approaches: swing block to the right (SWBR), swing block to the left (SWBL), shuffle block to the right (SHBR), shuffle block to the left (SHBL) and a stationary blocking approach (SBA). Each approach style was randomly ordered and separated by 1-2 minutes for recovery to allow optimal rest. A 3' × 8' force plate (Rice Lake Weighing Systems, Rice Lake, WI) with a data acquisition system (BioPac MP 150, Goleta, CA) sampling at 1,000 Hz was used to collect GRF data. A stationary volleyball target was positioned 10 cm above the volleyball net for all subjects. Repeated-measures ANOVAs with Tukey post-hoc comparisons were used to analyze the data (X ± SD, p < 0.05). Results: GRF data are presented below in Table 1. No significant differences were observed in peak concentric force, peak landing force and vertical jump height between any of the blocking approaches. Peak concentric and peak landing GRF were approximately 3-4 times greater when compared to the average subjects' body weight. SWBR and SWBL demonstrated greater rates of force development (RFD) when compared to SBA and SHBL. Impulse was lower for SBA when compared to all other blocking approaches, while no other differences were observed. Conclusions: Based on our results we can assume that higher RFD for SWBR and SWBL may allow athletes to reach the blocking height in a shorter time frame due to ability to develop large forces over a shorter period of time. No differences in vertical jump height were observed as subjects were jumping to a stationary set volleyball target positioned at a consistent height above the volleyball net. Practical Applications: These data can be used by strength and conditioning coaches in order to obtain a better insight into volleyball kinematic requirements, especially considering that peak concentric and peak landing GRF can reach a magnitude of 3-4 times subjects' body weight. These findings can provide a solid foundation for resistance training program development and serve as a guideline for choice of resistance training exercises that create similar GRF values obtained in this study in order to optimize on-court performance.